Cryopreservation in rhinoceros-Setting a new benchmark for sperm cryosurvival. - Robert Hermes; Thomas Bernd Hildebrandt; Frank Göritz (PLoS ONE)
At times when rhinoceros are fiercely poached, when some rhinoceros species are closer than ever to extinction, and when the scientific community is in debate over the use of advanced cell technologies as a remaining resort it is time to simplify and improve existing assisted reproduction techniques to enhance breeding and genetic diversity in the living populations under our care. Semen cryopreservation has been performed in all captive rhinoceros species with limited degree of success. Here we tested three freezing extenders, containing different cryoprotectants and various freezing rates for the cryopreservation of rhinoceros sperm from 14 bulls. In experiment I, semen from 9 bulls was used to determine the most suitable diluent, cryoprotectant and freezing rate for the successful cryopreservation of rhinoceros sperm. In experiment II, semen from 5 bulls was used to assess whether the removal of seminal plasma could further improve post thaw sperm quality following cryopreservation with conditions identified in Experiment I. Semen was diluted with Berliner Cryomedia, ButoCrio® or INRA Freeze®, packaged in 0.5 mL straws and frozen 3, 4, and 5 cm over liquid nitrogen (LN) vapour or directly in a dryshipper. It was found that semen extended with ButoCrio® (containing glycerol and methylformamide) and frozen 3cm over LN vapour provided the best protection to rhinoceros spermatozoa during cryopreservation. When pooled over treatments, total and progressive post thaw motility was 75.3 ± 4.2% and 68.5 ± 5.7%, respectively marking a new benchmark for the cryopreservation of rhinoceros sperm. Post thaw total and progressive motility, viability and acrosome integrity of semen diluted in ButoCrio® was significantly higher than semen extended in Berliner Cryomedia or INRA Freeze®. The removal of seminal plasma did not improve post thaw sperm survival (p > 0.05). In conclusion, the cryosurvival of rhinoceros spermatozoa was significantly improved when using a mixture of glycerol and methylformamide in combination with a fast freezing rate at 3 cm. These results describe a new protocol for the improved cryosurvival of rhinoceros spermatozoa and will enable a more successful preservation of genetic diversity between males, especially in donors whose spermatozoa may already be compromised prior to or during collection. The successful reduction of glycerol concentration in favour of methylformamide as a cryoprotectant could be a novel suggestion for the improvement of cryopreservation techniques in other wildlife species.